Almas’ story : a young muslim refugee girl’s experiences as newcomer in Northern-Finland - Pagés, Eugenia Carratalá (fi=Lapin yliopisto|en=University of Lapland|, 2016)
Northern Finland is a homogeneous social context with short tradition of hosting immigrants. This narrative social work research focuses on “what it means to live as a newcomer in society unaccustomed to migration” by exploring the everyday experiences and social interactions of Almas, a young Muslim girl with a diasporic background living in northern Finland. The wider goal of the work is to bring migrant subjective voices and diverse narratives to social work knowledge production as a new type of inclusive bottom-up social work research. Theoretical frame of the research is based on the interpretivist research paradigm, critical social science and holistic narrative social work. The narrative analysis of Almas´ personal story is used for building connections between the individual and larger social structures in a homogeneous society. The findings reveal concerning dynamics resulting from power imbalances in everyday interactions between the Finnish majority and immigrant minority. Almas’ social encounters and ordinary interactions are commonly characterized by everyday discrimination and covert racism practices. The main findings suggest that consequence of Almas being excluded in homogeneous Finnish context is related to a larger negative appreciation of cultural differences, racialized categorization of the immigrant “Other”, as well as the failure of top-down politics of mlticulturalism, which assumes the integration happening spontaneously when people share the same physical space. Thus, including migrant voices in inclusive social work research knowledge production helps developing more effective strategies towards acknowledgment of cultural differences and mutual understanding in quick growing social diversity contexts like northern Finland.